In vitro termination of adenovirus DNA synthesis by a soluble replication complex. - Arens, M (1978)
The double-stranded DNA from a soluble DNA replication complex that was labeled with deoxyribonucleoside triphosphates and completed in vitro was digested with EcoRI, Sma I, and Hpa I restriction endonucleases. All regions of the adenovirus type 2 genome were labeled in vitro, but restriction fragments derived from the ends of the DNA molecules were relatively more highly labeled than those derived from internal regions. The in vitro endogenous DNA polymerase reaction also exhibited strand-specific labeling near the molecular ends, in that restriciton fragments from the left end were labeled predominantly in the r strand and fragments from the right end were labeled predominantly in the l strand.